Implementation of assessment for learning to improve students’ cognitive learning outcomes in the concept of chemical bonding - Siti Mutmainah; Muchlis Muchlis (Jurnal Pijar Mipa, 2022)
The purpose of this study is to describe the implementation of Assessment for Learning-based Learning, student activities, improving cognitive learning outcomes, and student responses after applying Assessment for Learning-based education. The type of research is a pre-experimental research design with one group pretest-posttest design. The research subjects were 39 high school students. The Assessment for Learning-based Learning implementation during the first, second and third meetings was very well carried out with 93.6%, 94.9%, and 98.6%, respectively. The students did suitable activities for three meetings by assessing learning principles with 94.9%, 92.9%, and 97.0%. After implementing Assessment for Learning-based Learning, the increase in student learning outcomes was as many as 92.3% of students in the high n-gain category. 7.7% of students in the medium n-gain category and 94.8% passed classical learning completeness. Student responses to Assessment for Learning-based Learning get a good response with a percentage of 89%. In conclusion, Assessment for Learning-based Learning can improve the learning outcomes of 10th grade students on the chemical bonding material.